Urban compactness and Land Use Efficiency in Indochina Capitals: A multi-method spatial assessment (2017–2024) - Tran Tuan Nguyen (PLoS ONE, 2026)
This study assesses land use efficiency (LUE) and urban spatial structure in three Indochina capitals, Hanoi, Vientiane, and Phnom Penh, during the period 2017–2024. By integrating the SDG 11.3.1 indicators with spatial agglomeration analysis (global Moran’s I) and urban form measurement (Polsby-Popper index), the study provides a multidimensional assessment of urban expansion patterns. The results indicate that land expansion outpaces population growth in all three cities (LUE > 1). Phnom Penh exhibited the highest LUE value (5.03), strong spatial agglomeration, and the most compact urban form. Hanoi recorded the lowest LUE (2.47), characterized by moderate compactness and weak spatial autocorrelation. In contrast, Vientiane displayed fragmented and largely random urban expansion, accompanied by a declining compactness index and no statistically significant agglomeration. These contrasting patterns reflect distinct urban development trajectories shaped by differences in planning regimes, land management practices, and investment orientations. The findings highlight the urgent need for spatially controlled and compact urban development strategies in rapidly growing cities, while also acknowledging data limitations. The proposed analytical framework is transferable and can be applied to other developing cities worldwide.